An Investigation into How Fluctuations in Global Crude Oil Prices Impact Tadawul All-Shares Index (TASI) (January 1995-December 2017) - Al-Ghanmi, Alyaa Talal (Journal of Economic, Administrative and Legal Sciences, 2024)
This paper investigates the effect of fluctuations in the global oil market on the movement of the TADAWUL All Shares Index, TASI, by using monthly data for the period between January 1995 and December 2017. To capture the impact of the global oil market, this paper uses the two main benchmarks in the global oil market, West Texas Intermediate (WTI), and Brent Crude oil. As the stock market is known to be stochastic, a set of secondary explanatory variables is added to this research. It consists of the following: inflation rates, short-term interest rates, gold spot prices, level of imports, level of funds invested in private securities by the private sector, and proxy for global equity markets, FTSE 100. The FTSE 100 has a significant impact on the TASI index, the coefficient is close to 1. The significant impact of the FTSE 100 on the TASI index could signal the existence of many dual investors in both indices. The results show that all variables have an impact on the TASI index at a statistically significant level. Despite the positive impact of spot prices on both benchmarks, the futures strip curve for both benchmarks are inversely related to the predicted variable. Also, the TAIS index is more exposed to changes in the WTI than changes in Brent Crude. It is clearly shown in the coefficient values, .359 and .302, for WTI and Brent Crude respectively.  Moreover, over the sample period there is an increase in the level of the explained variation in the TASI index by the explanatory variable. This would indicate that TASI has become a less speculative and more sophisticated market. Finally, as this paper provides evidence for the impact of the global equity market on TASI, it would open a window for future research to examine the impact of other international equity markets on TASI.
Keywords: TASI; WTI; BRENT Crude; Oil Futures; REOP Rate